Long-term analysis of the environmental effects on the global dynamic properties of a hybrid timber-concrete building. (1st October 2022) - Larsson, Carl; Abdeljaber, Osama; Bolmsvik, Åsa; Dorn, Michael
Highlights: This article presents three years of environmental and structural observations in a timber-concrete hybrid building. Results show a clear seasonal variation in natural frequencies over time. Moisture content within a cross-laminated timber slab correlates significantly with the natural frequencies of the building. A predictive model for the natural frequencies is presented, taking seasonal variations and a dry-out of the structure into account. Abstract: With the increased availability of timber materials, such as cross-laminated timber, the number of buildings using timber as a structural material has been rapidly increasing. As these buildings are new to the market, limited data and research on their long-term structural modal performance are available. This is particularly important in timber buildings since the material properties of wood are highly affected by environmental factors, especially the moisture content. Over time, the evolution of the dynamic properties is essential for damage indication in structural health monitoring systems since natural changes can mask the influence of damage. This work presents three years of observations from a structural monitoring system collecting data ever since completing a four-story timber-concrete hybrid building in Sweden. Ambient vibrations of the building were measured using geophones, resulting in 3, 100 datasets. The temperature and relative humidity were measured both externally using a weather station and internally using sensors embedded in several walls and a slab in the building. The observed natural frequencies of the building vary with ± 0.2 Hz around the mean value over time. Linear regression analysis shows a significant correlation between the moisture content of a cross-laminated timber slab and the natural frequencies (coefficient of determination R 2 up to 0.84). A predictive model for the natural frequencies is presented, taking seasonal variations and a dry-out of the structure into account. Variations from the expected values are ± 0.1 Hz at most. The model clearly narrows the error margins for damage indication in a structural health monitoring system.